Analisis Efisiensi Belanja Negara Periode 2014 – 2016 Di PSTNT-BATAN - Sakti Muda Nasution (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2020)
This research entitled " Analysis of State Expenditure Efficiency on Budget Realization Report for 2014-2016 period in PSTNT BATAN Bandung ". The research as outlined in this Final Assignment aims to determine the State Expenditure Efficiency on Budget Realization Report for 2014-2016 period in PSTNT BATAN Bandung. The research method used is descriptive analysis method that the authors describe the results of observation and analyze the data obtained in the field. After analyzing and discussing the problem, the writer concludes that the State Expenditure Efficiency on Budget Realization Report for 2014-2016 period in PSTNT BATAN Bandung can be categorized as "Highly Efficient".